Endogenous growth and intellectual property rights: a North-South modelling proposal - Azevedo, Mónica (2017)
In what form should the Intellectual Property Rights (IPR) be treated in an endogenous growth model? What are the effects of introducing IPR into a North-South endogenous growth model? In this paper, we develop a general equilibrium endogenous growth model that emphasizes the IPR enforcement effects on growth, in a scenario of North-South technological knowledge diffusion. The economy consists of three sectors, and firms are engaged in step-by-step innovation. In line with the literature, we introduce an IPR parameter that makes imitation more difficult. We find that, in steady state, the increases in IPR protection result in decreases in the growth rate. This result is in line with the literature, which argues that the enforcement of IPR does not always have a positive effect on economic growth and highlights that there is much more work to be done in this field of study, given that the existing results are not consensual. To sum up, we present some suggestions for future research which can help to clarify the relationship between IPR and endogenous growth.